A Formação Translíngue do Tradutor-Intérprete de Língua Brasileira de Sinais nas aulas de inglês - DANIEL PEREIRA MATIAS (2024)
The area of research into Deaf Studies has progressively increased in recently, particularly due to the use of the Brazilian Sign Language (Libras) and social inclusion in a wide range of social contexts (Negreiros, 2021; Nogueira, 2018; Quadros, 2017; Favorito, Silva, 2017). It is worth investigating the linguistic and critical training (Cervetti, Pardales, Damico, 2001) of the professional Sign Language Translator-Interpreter (TILS, in Portuguese) who works in the school classroom, with an emphasis on teaching English to the deaf, from a translanguaging perspective (García, Alvis, 2019, Takaki, 2020)/translingual practices (Canagarajah, 2013a, 2013b). Therefore, this master's research aimed to conduct an autoethnographic, qualitative, interpretative and exploratory investigation (Ono, 2017) into the education of the Brazilian Sign Language Translator-Interpreter (the TILS being the researcher and author of this project) for English classes in the 3rd (last) year of high school in a public school through translanguaging/translingual practices, during the second semester of 2023, in Campo Grande - MS. Keywords: Education of the Brazilian Sign Language Translator-Interpreter, Translanguaging, Decoloniality.